BENTUK POLA ASUH OTORITER ORANGTUA PEKERJA BURUH PABRIK SEPATU DI DESA PECANGAAN - Anni Roi Khatul Jannah; Khamdun (Jurnal Prasasti Ilmu, 2025)
This study examines the impact of authoritarian parenting patterns applied by parents of hoe factory workers on the formation of children's independent character in Pecangaan Village. Using a qualitative narrative approach with observation methods, in-depth interviews, and documentation, this study found that authoritarian parenting patterns are characterized by giving orders and prohibitions to children, high demands in terms of independence, parents have high standards that must be met by children, parents punish verbally or non-verbally when breaking the rules at home, parents do not give children the opportunity to make their own decisions. The results of the study showed that children who were raised with authoritarian parenting patterns tended to have low levels of independence, high dependency, and difficulty in managing emotions and making decisions independently. Although this parenting pattern is able to form discipline, pressure and lack of effective communication between parents and children hinder the development of independent character. This study concludes that a balance is needed between supervision and freedom in parenting, and recommends parents to adopt a more democratic and communicative parenting pattern in order to create an environment that supports the development of children's character.